Long-term sildenafil therapy for pulmonary veno-occlusive disease in association with melphalan therapy for multiple myeloma: A case report - Christian Hesse; Gabor Kovacs; Stefan Scheidl; Horst Olschewski (SAGE Open Medical Case Reports)
Pulmonary veno-occlusive disease has a significantly worse prognosis than idiopathic pulmonary arterial hypertension. According to a case series from France, the median survival time from diagnosis to death or lung transplantation was only 1 year, and in a more recent analysis, pulmonary arterial hypertension therapy had no significant effect on survival. There are case reports and case series describing both beneficial and adverse effects of pulmonary arterial hypertension-related medications. The most life-threatening complication of such a therapy is pulmonary oedema. In the long term, lung transplantation remains the best treatment option for suitable patients. However, elderly patients with concomitant or precipitating malignant disease are not considered transplant candidates. We describe a 59-year-old pulmonary veno-occlusive disease patient with multiple myeloma in World Health Organisation functional class IV who was successfully treated with sildenafil for almost 5 years.